EFFECT OF QIANLIE XIAOZHENG TANG, A CHINESE HERBAL DECOCTION, ON CASTRATION RESISTANT PROSTATE CANCER: A PILOT STUDY - Pang, Ran; Gao, Xiaosong; Lu, Jianxin; Zhang, Yaqiang (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: To examine the effect of Qianlie Xiaozheng Tang (QLXZT), a Chinese herbal decoction, on treating castration resistant prostate cancer (CRPC). Materials and Methods: A total of 70 men with CRPC were recruited and randomly allocated into treatment groups (treated with QLXZT and conventional therapy) or control group (treated with conventional therapy) for 12 weeks treatment. Primary endpoint was serum prostate specific antigen (PSA) concentration. Secondary endpoints included patients’ quality of life measured by Functional Assessment of Cancer Therapy-Prostate questionnaire, and prostate cancer-specific anxiety assessed by Memorial Anxiety Scale for Prostate Cancer. Results: After a 12-week treatment, the PSA level in control group rose remarkably from 45.3 ± 17.0 to 76.0 ± 56.7 ng/ml (P=0.0015). By contrast, the PSA level in treatment group did not increase significantly (P>0.05). The scores of Functional Assessment of Cancer Therapy-Prostate in each domain changed significantly (P<0.05) in treatment group whereas the scores in control group did not differ from the baseline. In addition, the scores of Memorial Anxiety Scale for Prostate Cancer in treatment group dropped from 30.5 ± 4.7 to 27.0 ± 3.9 (P<0.001) while no significant difference was found between baseline and post-treatment in control group (P>0.05). Conclusions: QLXZT could slow PSA progression, enhance quality of life and alleviate the prostate cancer-specific anxiety in patients with CRPC.